Noncommutative Lightweight Signcryption for Wireless Sensor Networks - Lize Gu; Yun Pan; Mianxiong Dong; Kaoru Ota (International Journal of Distributed Sensor Networks)
Key management techniques for secure wireless-sensor-networks-based applications must minimally incorporate confidentiality, authenticity, integrity, scalability, and flexibility. Signcryption is the proper primitive to do this. However, existing signcryption schemes are heavyweight and not suitable for resource-limited sensors. In this paper, we at first propose a braid-based signcryption scheme and then develop a key establishment protocol for wireless sensor networks. From the complexity view, our proposal is 2 15 times faster than RSA-based ones. As far as we know, our proposal is the first signcryption scheme based on noncommutative algebraic structures.